Factors Affecting the Implementation of Developmental Care in the Care of Premature Babies in NICU Nurses: A Systematic Review - CH.R. Yeni Suryandari; Yuni Sufyanti Arief; Sri Utami (Universitas Airlangga, 2021)
Introduction: Developmental care-based preterm infant care management that aims to protect the neurological system and reduce adverse effects has developed over the last few decades. The study aimed to explore the factors that influence the implementation of developmental care among NICU nurses.Methods: The study was systematically identified by searching an electronic database using keywords